"Set It and Forget It" Hydroponic Lettuce - Hannah Wooten (EDIS)
Florida ranks second in the United States for vegetable production, and the second largest industry in Florida is agriculture. However, the on-going loss of agricultural land to development, increasing labor costs, and decreasing water resources creates a need for alternative agricultural systems. Hydroponic food production can produce similar yields as traditional agriculture using less water, land, and labor. Equipping urban audiences with tools to grow food hydroponically provides new options for feeding the growing urban population in non-traditional environments. "Set it and forget it" hydroponics is a simple, affordable, and successful introductory hydroponic method. This technique is great for growers new and experienced and is especially well adapted for classroom experiments.